2007
DOI: 10.2176/nmc.47.229
|View full text |Cite
|
Sign up to set email alerts
|

Complete Response to Temozolomide Treatment in an Elderly Patient With Recurrent Primary Central Nervous System Lymphoma-Case Report-

Abstract: An 80-year-old woman presented with primary central nervous system (CNS) lymphoma manifesting as progressive disorientation and loss of activity. She received three cycles of high-dose methotrexate. The tumor shrank after two cycles and her mental status improved, but she suffered tumor recurrence. The second-line treatment consisted of four cycles of rituximab but the tumor enlarged. She was then treated with three cycles of temozolomide. Magnetic resonance imaging revealed no evidence of disease. Her mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bruton tyrosine kinase inhibitor ibrutinib was introduced as a novel effective agent to PCNSL, especially to B-cell type lymphoma. 24) Temozolomide (TMZ) treatment or immunotherapy might be one of the selections for lymphomatosis cerebri as an adjuvant treatment following MTX therapy, 15,[25][26][27] although the effect of TMZ on PCNSL has not yet been proven. When an effective treatment for lymphomatosis cerebri is established, improvement of the patient's cognitive function can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Bruton tyrosine kinase inhibitor ibrutinib was introduced as a novel effective agent to PCNSL, especially to B-cell type lymphoma. 24) Temozolomide (TMZ) treatment or immunotherapy might be one of the selections for lymphomatosis cerebri as an adjuvant treatment following MTX therapy, 15,[25][26][27] although the effect of TMZ on PCNSL has not yet been proven. When an effective treatment for lymphomatosis cerebri is established, improvement of the patient's cognitive function can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Alkylating agents are generally effective against non-Hodgkin's lymphoma and temozolomide has good CNS penetration and a favorable toxicity profile [9,10]. The use of single-agent temozolomide as salvage therapy for PCNSL has been described in case reports [11][12][13] and a phase II trial assessed the activity of single-agent temozolomide in patients with recurrent PCNSL [14]. These findings suggested that temozolomide as a promising salvage treatment for refractory or relapsed PCNSL.…”
Section: Introductionmentioning
confidence: 99%